Insights from the Labor Module on Work and Wages in Cox's Bazar - World Bank (World Bank, Washington, DC, 2021)
The labor market module was administered as part of the adult questionnaire of the Cox’s Bazar Panel Survey to 2 randomly selected adults from every household in the sample, amounting to a total of 9,045 individuals. The module generates representative statistics for the adult (15+) population of hosts and displaced Rohingya in Cox’s Bazar; and it can be further disaggregated into hosting areas with low and high exposure to the Rohingya influx, and by gender. Besides collecting information on the participation of adults in the labor force and their employment status, the module collects details on wage and non-wage employment, wage rates, sectors of employment and barriers faced in obtaining work.